Juridical analysis of user consumer protection health services (case study of Tiara Debora Simanjorang's death in hospital Kalideres family partner) - Maurits Barita Parlindungan; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
Hospitals providing their services must pay attention to the quality of their services to patients as consumers. A large number of demands and lawsuits from patients to the hospital is clear evidence that there are still many patients who are dissatisfied with the services provided by the hospital. The problem that arises in the health services provided by the Kalideres Family Partner Hospital to Debora is the provision of services that are not optimal, causing losses to patients. The main problems in this study are 1) Whether there is a violation of consumer rights, and 2) How consumers can take efforts for the losses experienced. To answer the subject matter, normative research is carried out, data processing is carried out qualitatively, concluding using a deductive mindset. The conclusion of the study is 1) Violations of consumer rights occur due to the obligations of the Hospital as a service provider that are not done properly, namely not providing services to Debora safely, properly, and without discrimination, and 2) The efforts that can be taken by consumers based on applicable laws and regulations are through peace agreements, through the Consumer Dispute Resolution Agency and the courts.